Evaluation Of The Implementation Of Mental Health Program at P Community Health Center in 2022 - Elmi Astrabel; Ahmad Hanafi; Uvirda (JURNAL KESMAS DAN GIZI (JKG), 2024)
Abstract This research aims to evaluate the implementation of the Mental Health Program at Payung Sekaki Community Health Center in 2022, using a qualitative approach and a descriptive design. Involving informants with relevant competencies, including the Head of the Community Health Center, the Mental Health Program Manager, mental health cadres, and patient families, data were collected through interviews. The research was conducted in November and December 2023 at Payung Sekaki Community Health Center. Qualitative data analysis utilized triangulation methods, involving source, method, and data triangulation to ensure the validity of the results. The evaluation revealed that the performance achievements were below the target, with main obstacles related to resource aspects, team coordination, and community awareness. These findings emphasize the need for in-depth evaluation, coordination improvement, enhanced training, and a comprehensive approach to raise community awareness regarding mental health at Payung Sekaki Community Health Center.